Hidrolisis minyak jarak pada tekanan tinggi (hydrolysis of castor oil at high pressure) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The solubility of water in oil increases with temperature. Therefore, at high temperatures no catalyst is required to promote the reaction of water and oil. This experiment was to investigate the effect of reaction temperature and water to oil ratio on the hydrolysis of castor oil. Hydrolysis was undertaken in an autoclave, provided with stirrer, heating system, temperature controller and sampling device. Experiment was started by introducing 100 mL of castor oil and 100 mL of water into the autoclave, set the stirrer motor speed at 500 rpm and the temperature at a specified value and then the heat source was switched on. After the specified temperature was attained, samples were taken at 15 minutes intervals to analyse the free fatty acid contents. The conversions increased with reaction time and temperature. The effect of temperature was more pronounced compared with the effect of water to oil ratio. The kinetics of hydrolysis of castor oil was a pseudo first order reaction, and the relation between reaction rate constant and temperature followed Arrhenius equation and can be expressed as: k =.1205.5 e- 11,894.58/RT min-1 with an error of 7.68 %. The activation energy agreed fairly well with the values at the previous works.